Country, Native Title and Ecology - K. Weir, Jessica (ANU Press, 2012)
Country, native title and ecology all converge in this volume to describe the dynamic intercultural context of land and water management on Indigenous lands. Indigenous people's relationships with country are discussed from various speaking positions, including identity and knowledge, the homelands debate, water planning, climate change and market environmentalism. The inter-disciplinary chapters range from an ethnographic description of living waters in the Great Sandy Desert, negotiating the eradication of yellow crazy ants in Arnhem Land, and legal analysis of native title rights in emerging carbon markets. A recurrent theme is the contentions over meaning, knowledge, and authority. "Because this volume is scholarly, original and very timely it represents a key resource and reference work for land and sea managers; policy makers; scholars of the interface between post-native title responsibilities, NRM objectives and appropriate heritage protocols; and students based in the social sciences, natural sciences and humanities. It is rare for volumes to have this much cross-academy purchase and for this reason alone - it will have ongoing worth and value as a seminal collection." - Associate Professor Peter Veth, ANU College of Arts and Social Sciences, The Australian National University. Dr Jessica Weir has published widely on water, native title and governance, and is the author of Murray River Country: An Ecological Dialogue with Traditional Owners (Aboriginal Studies Press, 2009). Jessica's work was recently included in Stephen Pincock's Best Australian Science Writing 2011. In 2011 Jessica established the AIATSIS Centre for Land and Water Research, in the Indigenous Country and Governance Research Program at the Australian Institute of Aboriginal and Torres Strait Islander Studies.